Analisis Pemanfaatan Jurnal Elektronik Sebagai Sumber Belajar Oleh Mahasiswa Universitas Muhammadiyah Sumatera Utara - Manurung, Asmita Khoiriyah; Sayekti, Retno; Syam, Abdi Mubarak (Jurnal Ilmiah Wahana Pendidikan, 2024)
The use of e-journals includes user activities in utilizing journals as a means of obtaining the necessary information. Information in journals is scientific and up-to-date, covering various branches of science. Currently, journals have been provided in electronic versions that ca n be accessed in various ways, which in terms of access are divided into two categories, namely open access e-journals and closed access e-journals. In this study, researchers have the aim of analyzing the use of e-journals as a source of student learning, to what extent is the effectiveness, efficiency, and satisfaction of these electronic journals for students at Muhammadiyah University of North Sumatra with a measurement method utilizing the System Usability Scale (SUS).